2018
DOI: 10.1039/c8tb01196f
|View full text |Cite
|
Sign up to set email alerts
|

A novel thixotropic magnesium phosphate-based bioink with excellent printability for application in 3D printing

Abstract: A novel magnesium phosphate-based gel (TMP-BG) with excellent printability was developed for application in 3D printing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 65 publications
1
35
0
Order By: Relevance
“…Finally, the last three papers use polycaprolactone (PCL) (Lin et al, 2016 ), a blend of polyurethane (PU), PCL, poly(L-lactic acid) (PLLA) and poly[D,L-lactic acid] (PDLLA) (Hsiao and Hsu, 2018 ), and Thixotropic Magnesium Phosphate-based gel (TMP-BG) (Chen et al, 2018 ). This last hydrogel is prepared mildly (gelling method) with inorganic compound and thixotropic features that obtains promising results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the last three papers use polycaprolactone (PCL) (Lin et al, 2016 ), a blend of polyurethane (PU), PCL, poly(L-lactic acid) (PLLA) and poly[D,L-lactic acid] (PDLLA) (Hsiao and Hsu, 2018 ), and Thixotropic Magnesium Phosphate-based gel (TMP-BG) (Chen et al, 2018 ). This last hydrogel is prepared mildly (gelling method) with inorganic compound and thixotropic features that obtains promising results.…”
Section: Resultsmentioning
confidence: 99%
“…From those 16 papers, six of them perform cross-linking at 37°C (Ren et al, 2016 ; McBeth et al, 2017 ; Law et al, 2018 ; Tijore et al, 2018a , b ; Zheng et al, 2018 ) and three use room temperature (Köpf et al, 2016 ; Lin et al, 2016 ; Berg et al, 2018 ). The rest use thermal cross-linking without specifying temperature (Fan et al, 2016 ; Giuseppe et al, 2017 ; Bandyopadhyay et al, 2018 ; Chen et al, 2018 ; Cochis et al, 2018 ; Xu X. et al, 2018 ). On the other hand, in alginate/gelatin hydrogels Berg et al ( 2018 ) uses room temperature, He et al ( 2016 ) uses a cool substrate, and Bandyopadhyay et al ( 2018 ) and Giuseppe et al ( 2017 ) use thermal cross-linking but without specific temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[163] Another method for fabricating the MgP scaffold was based on the EB system, which stacks MgP slurry layer by layer into a 3D structure. [164,165] This method is simple and usually molded by utilizing the self-curing capability of MgP, so the printed structure has better biocompatibility and osteogenic activity. Ju-Ang Kim et al fabricated MgP scaffolds with different pore sizes and found that the scaffolds were completely degraded after 4 weeks of implantation in rabbit skull defect sites with simultaneous bone regeneration.…”
Section: Sls 1200°c 4 Hmentioning
confidence: 99%
“…[ 163 ] Another method for fabricating the MgP scaffold was based on the EB system, which stacks MgP slurry layer by layer into a 3D structure. [ 164,165 ] This method is simple and usually molded by utilizing the self‐curing capability of MgP, so the printed structure has better biocompatibility and osteogenic activity. Ju‐Ang Kim et al.…”
Section: Materials Used In Bone Reconstruction By Ammentioning
confidence: 99%